2023
DOI: 10.3390/cryst13040584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crack Formation on the Mechanical Properties of Bilayer Graphene: A Comparative Analysis

Abstract: We present a molecular dynamics simulation study on the effects of crack formation on the mechanical properties of bilayer graphene. Bilayer graphene possesses unique electronic properties that can be modified by applying a voltage, making it an attractive material for various applications. We examined how the mechanical properties of bilayer graphene vary under various crack configurations and temperatures, measuring Young’s modulus, fracture toughness, fracture strain, and fracture stress. We compared the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Comparing previous studies on bilayer graphene [42], it was found that when the number of atoms is the same in a monolayer, the fracture stress of bilayer graphene is less than that of monolayer graphene. The same situation exists when comparing monolayer irida graphene with bilayer irida graphene.…”
Section: Monolayer Comparison Of Ge and Igmentioning
confidence: 63%
“…Comparing previous studies on bilayer graphene [42], it was found that when the number of atoms is the same in a monolayer, the fracture stress of bilayer graphene is less than that of monolayer graphene. The same situation exists when comparing monolayer irida graphene with bilayer irida graphene.…”
Section: Monolayer Comparison Of Ge and Igmentioning
confidence: 63%
“…Sun et al [ 49 ] investigated the impact of vacancy defects on the mechanical characteristics of graphene, revealing that vacancy defects induce stress concentration, leading to a reduction in failure strength by approximately 17.7% due to a single vacancy. Yu et al [ 50 ] conducted a comparative analysis on the influence of geometric shape and orientation of cracks on the mechanical properties of graphene. Yin et al [ 51 ] explored the applicability of the Griffith criterion, designed for continuous medium theory, in discrete atomic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based materials have garnered significant attention due to their versatile and promising applications, in particular, extensive research has focused on the exploration of two-dimensional (2D) carbon materials [ 1 , 2 , 3 ]. The excellent mechanical properties have been widely studied in many aspects, for example, the tensile strength on monolayer and bilayer graphene, the defect influence, the magic angle graphene and the phase transition induced by strain [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. On the other hand, the fullerene system is one of the prominent candidates for future electronic applications as recently proposed in [ 26 ].…”
Section: Introductionmentioning
confidence: 99%